GATA2 deficiency and haematopoietic stem cell transplantation: challenges for the clinical practitioner. (11th November 2019) - Bogaert, Delfien J.; Laureys, Genevieve; Naesens, Leslie; Mazure, Dominiek; De Bruyne, Marieke; Hsu, Amy P.; Bordon, Victoria; Wouters, Erik; Tavernier, Simon J.; Lambrecht, Bart N.; De Baere, Elfride; Haerynck, Filomeen; et al.
Summary: GATA2 deficiency, first described in 2011, is a bone marrow failure disorder resulting in a complex haematological and immunodeficiency syndrome characterised by cytopenias, severe infections, myelodysplasia and leukaemia. The only curative treatment is allogeneic haematopoietic stem cell transplantation (HSCT). Although knowledge on this syndrome has greatly expanded, in clinical practice many challenges remain. In particular, guidelines on optimal donor and stem cell source and conditioning regimens regarding HSCT are lacking. Additionally, genetic analysis of GATA2 is technically cumbersome and could easily result in false‐negative results. With this report, we wish to raise awareness of these pitfalls amongst physicians dealing with haematological malignancies and primary immunodeficiencies.